Nonlinear dynamics of mood regulation in bipolar disorder. (13th August 2014) - Ortiz, Abigail; Bradler, Kamil; Garnham, Julie; Slaney, Claire; Alda, Martin
<x xml:space="preserve">Abstract</x> Objectives We sought to study the underlying dynamic processes involved in mood regulation in subjects with bipolar disorder and healthy control subjects using time‐series analysis and to then analyze the relation between anxiety and mood using cross‐correlation techniques. Methods We recruited 30 healthy controls and 30 euthymic patients with bipolar disorder. Participants rated their mood, anxiety, and energy levels using a paper‐based visual analog scale; and they also recorded their sleep and any life events. Information on these variables was provided over a three‐month period on a daily basis, twice per day. We analyzed the data using Box–Jenkins time series analysis to obtain information on the autocorrelation of the series (for mood) and cross‐correlation (mood and anxiety series). Results Throughout the study, we analyzed 10, 170 data points. Self‐ratings for mood, anxiety, and energy were normally distributed in both groups. Autocorrelation functions for mood in both groups were governed by the autoregressive integrated moving average (ARIMA) (1, 1, 0) model, which means that current values in the series were related to one previous point only. We also found a negative cross‐correlation between mood and anxiety. Conclusions Mood can be considered a memory stochastic process; it is a flexible, dynamic process that has a 'short memory' both in healthy controls and euthymic patients with bipolar disorder. This process may be quite different in untreated patients or in those acutely ill. Our results suggest that nonlinear measures can be applied to the study of mood disorders.